Influence of socioeconomic indicators on the COVID-19 pandemic in the child and youth population - Ana Cristina Ribeiro; Isa Milene Vansan Falciroli; Rodrigo das Neves Cano; Sílvia Carla da Silva André Uehara (Universidade Federal do Ceará, 2024)
Objective: to analyze the influence of socioeconomic indicators on the COVID-19 pandemic in the child and youth population. Methods: this is an ecological study, considering all reported cases of COVID-19 infection and deaths in children and adolescents. Secondary data was collected and analyzed using the Global Moran's Index, both univariate and bivariate. Results: the highest incidence rate of COVID-19 in the child and youth population was recorded in the Midwest; the highest mortality rate was found in the North; and the highest lethality rate was reported in the Northeast. There was also a negative correlation between COVID-19 mortality in the child and youth population and the Human Development Index, per capita income, and education level of the head of the household. Conclusion: Socioeconomic indicators related to the Human Development Index (HDI), nominal per capita income, and education level of the head of the family may have influenced the increase in incidence and mortality from COVID-19 in the child and youth population in Brazil. Contributions to practice: knowledge of regional socioeconomic inequalities helps to plan and implement public policies aimed at minimizing Brazil's regional inequalities in the face of health crises such as those experienced during the COVID-19 pandemic.